The mitochondrial basis of ageing and neurodegeneration - Ingram, Thomas Liam (2020)
One of the greatest achievements of the past 150 years is the extraordinary extension of average human lifespan. However, increasing average lifespan is coupled to an insidious rise in age-related cognitive decline and muscle loss. Indeed, progressive age is the number one risk factor for non-communicable diseases. Understanding the underlying biological mechanisms which drive ageing is a mammoth task. Mitochondrial dysfunction has emerged as a critical feature of ageing. This Thesis explored the biochemical changes to mitochondria with age and diseases of age.